2009
DOI: 10.1007/s12308-009-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of C-REL expression in diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) with a germinal center B-cell (GCB) phenotype is believed to confer a better prognosis than DLBCL with an activated B-cell (ABC) phenotype. Previous studies have suggested that nuclear factor-κB (NF-κB) activation plays an important role in the ABC subtype of DLBCL, whereas c-REL amplification is associated with the GCB subtype. Using immunohistochemical techniques, we examined 68 newly diagnosed de novo DLBCL cases (median follow-up 44 months, range 1 to 142 months) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
0
21
1
2
Order By: Relevance
“…Curry et al 15 showed a worse OS in patients with c-Rel + GCB-DLBCL compared with that in patients with c-Rel − GCB-DLBCL. 15 Espinosa et al reported better outcome in patients with phosphorylated p65 + DLBCL compared with that in patients with p65 − DLBCL. 9 However, patients in these two studies were treated with chemotherapy without rituximab.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Curry et al 15 showed a worse OS in patients with c-Rel + GCB-DLBCL compared with that in patients with c-Rel − GCB-DLBCL. 15 Espinosa et al reported better outcome in patients with phosphorylated p65 + DLBCL compared with that in patients with p65 − DLBCL. 9 However, patients in these two studies were treated with chemotherapy without rituximab.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, most previous studies have evaluated only a subset of the NF-κB subunits. [8][9][10][11][12][13][14][15] There are only two studies using all five subunits in DLBCL-a cohort of 88 patients with DLBCL by Odqvist et al 16 and a cohort of 45 patients with testicular DLBCL by Menter et al 17 In the current study, we evaluated expression of all five subunits of the NF-κB protein by immunohistochemistry and its clinical implications in a large cohort of patients with de novo DLBCL.…”
mentioning
confidence: 98%
“…20 Moreover, nuclear REL assessed by immunohistochemistry, was associated with worse clinical outcome in GCB DLBCL in a previous publication. 29 Those studies though were performed in biopsies from patients treated with chemotherapy without rituximab. As the addition of rituximab has markedly improved the overall survival rates in DLBCL, and the outcome of survival analyses depends on the clinical management, this can be a possible explanation for the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…In ABC-DLBCL, dysregulation of the NF-κB canonical and non-canonical pathways is associated with inferior prognosis [123, 125]. In GCB-DLBCL, patients with P52+ and P52+/RelB+ which activate the non-canonical pathway are associated with better overall survival and progressive-free survival than patients with P52- and P52-/RelB- [123]; A worse overall survival occurs in patients with c-Rel+ DLBCL, associated with the canonical pathway, compared with the survival of patients c-Rel-tumors [126]. However, there are heterogeneous expression patterns in many patients and there are no well characterized studies correlating each of these subtypes.…”
Section: Nf-κb Pathway and Different Types Of Lymphomamentioning
confidence: 99%